The Financial Cycle’s Conditions and Their Impact on ASEAN Macroeconomics in Covid-19 - Zahara, Vadilla Mutia; Suci, Stannia Cahaya; Suharto, Umayatu Suiroh (Tirtayasa Ekonomika, 2024)
The purpose of this study is to determine the condition of the financial cycle and their impact on macroeconomic developments such as economic growth in Indonesia and the ASEAN Region, especially in relation to the conditions of Covid-19 and post-Covid-19. The analytical method used in this study is the Panel Vector Error Correction Model (PVECM) to analyze long-term and short-term conditions and find out which variables have the most impact on the financial cycle in the ASEAN region. The variables that used in this study are variable housing credit, residential property price index, and the exchange rate as the independent variable, along with economic growth as the dependent variable. The data used is time series data with an analysis period of 2015 to 2022 with a quarterly data frequency. From these several variables, we suspect that there were stable cyclical conditions before Covid-19, and conditions that were shocked during Covid and post-Covid-19, if the credit cycle and exchange rate cycle are stable, then the financial index will be increasingly shaken. Research Stages namely, we will identify the problems in our research, then create a research design that we will test, then test the hypothesis using PVECM to prove the hypothesis, then interpret the results of the PVECM methods.